The Role of Scaffolding Assessment in Support of Self-Directed Learning in a Project-Based Learning of Research Class - Imam Santosa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study investigates the role of scaffolding assessment in fostering self-directed learning (SDL) within project-based learning (PBL) environments in higher education. Scaffolding assessment, characterized by gradual guidance, helps students transition from structured support to greater autonomy while enhancing critical thinking, goal-setting, and self-regulation. Through a mixed-methods approach, the study examines students' perceptions and experiences of scaffolding interventions in a research-based course. Quantitative findings reveal positive impacts on autonomy, critical thinking, and goal-setting, while qualitative insights highlight the importance of tailored scaffolding tools, motivational elements, and digital adaptability.Although scaffolding significantly enhances SDL by promoting independence and cognitive engagement, challenges remain in optimizing digital tools and addressing individual learning needs. Personalized scaffolding strategies and motivational scaffolds are essential for sustaining long-term engagement and effectively supporting diverse learners in complex, research-intensive environments. This study underscores the importance of adaptive scaffolding designs that balance structure and flexibility, offering practical implications for educators seeking to implement scaffolding assessments to enhance student autonomy and learning outcomes in higher education.